Grey matter density and GABAA binding potential show a positive linear relationship across cortical regions - Duncan, N.W.; Gravel, P.; Wiebking, C.; Reader, A.J.; Northoff, G. (Neuroscience, 2013)
► Combine GABAA receptor PET and grey-matter MRI imaging. ► Correlate BPND and VBM grey-matter densities. ► Show that regions with high GM density tend to have high GABAA BPND. ► Suggest at subject level that more variability in relationship may be present. Voxel based morphometry (VBM) is a widely used technique for studying the structure of the brain. Direct comparisons between the results obtained using VBM and the underlying histology are limited, however. To circumvent the problems inherent in comparing VBM data in vivo with tissue samples that must generally be obtained post-mortem, we chose to consider GABAA receptors, measured using 18F-flumazenil PET (18F-FMZ-PET), as non-invasive neural markers to be compared with VBM data. Consistent with previous cortical thickness findings, GABAA receptor binding potential (BPND) was found to correlate positively across regions with grey matter (GM) density. These findings confirm that there is a general positive relationship between MRI-based GM density measures and GABAA receptor BPND on a region-by-region basis (i.e., regions with more GM tend to also have higher BPND).